2017
DOI: 10.15386/cjmed-670
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Transvaginal Ultrasonography Compared to Endometrial Biopsy for the Etiological Diagnosis of Abnormal Perimenopausal Bleeding

Abstract: Background and aimsPerimenopause is marked by clinical manifestations which disturb everyday life and which may also hide a pathomorphological, more precisely endometrial, substrate. An accurate early diagnosis established by accessible, non-invasive methods is very important for the therapeutic management.MethodThe study included 103 patients aged between 41.5–55.11 years, divided into 3 age groups: 40–44 years (n=10), 45–49 years (n=54) and ≥50 years (n=39).ResultsCertain risk factors of endometrial neoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The study result is consistent with many other studies conducted across the globe, where fibroid uterus was the common condition associated with abnormal uterine bleeding. 12,20,21,[27][28][29] Unless uterine polyp, uterine fibroid develops during the reproductive age group, which would have contributed to the above finding, since majority of patients in this study were in the reproductive age group. Adenomyosis was the next common condition diagnosed by ultrasound which is also comparable with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study result is consistent with many other studies conducted across the globe, where fibroid uterus was the common condition associated with abnormal uterine bleeding. 12,20,21,[27][28][29] Unless uterine polyp, uterine fibroid develops during the reproductive age group, which would have contributed to the above finding, since majority of patients in this study were in the reproductive age group. Adenomyosis was the next common condition diagnosed by ultrasound which is also comparable with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…12 The results were consistent with numerous studies, where the ultrasound was as good as histopathology in the diagnosis of uterine fibroid in patients with abnormal uterine bleeding. 21,27,[30][31][32] However a study conducted by Hunter et al showed a sensitivity of 75% for USG in diagnosing uterine fibroid, even though it showed a specificity of 90%. 33 Similarly, a study conducted by Erdem et al showed a specificity of 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perimenopause is the time of women's life of natural shift from regular bleeding to anovulatory cycles with irregular and frequently excessive menstruation and eventually permanent infertility [ 5 ]. It usually starts 2-8 years before menopause and ends one year after [ 6 ]. Endometrial biopsy preceded by taking medical history, clinical examination and transvaginal ultrasound is a routine procedure in gynecological practice.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound [US] could play a role in the exclusion of organic lesions for AUB. This is important because AUB is the main etiology for hysterectomy and represents two-thirds of all hysterectomies [4] .…”
Section: Introductionmentioning
confidence: 99%